The Struggle Is Real: Propaganda and Workers Songbooks Published By the Workers Music League, 1934-35 - (:unkn) unknown (My University, 2015)
In New York City, the 1930s saw an explosion of artistic activity through the growth of literary John Reed Clubs, Workers Theatres, and in music: the Composers Collective and Pierre Degeyter Club. These music organizations can trace their roots ultimately back to the Communist Party of the United States, and then to Comintern. They worked together with the goal of creating a distinctly “proletarian music,” which arguably culminated in the 1934 and 1935 releases of two Workers Songbooks. Together, these Songbooks serve as examples of the organizations’ attempts to create proletarian music, and also as examples of neutral propaganda, as defined in the Epistemic Merit Model of propaganda by Sheryl Tuttle Ross. This can be shown by evaluating the writings of Collective members Charles Seeger and Aaron Copland, and by evaluating the Songbooks according to the parts of a neutral propaganda and an epistemically merited message, as outlined according to the Epistemic Merit Model.
Keywords: Communism; Composers Collective; Propaganda; Workers Songbooks